Normative goals, incentives and behaviour in economic decisions - Mohd Arshad, Mohd Nahar (Centre for Islamic Economics, KENMS, IIUM & International Institute of Islamic Thought, 2024)
In this chapter, we examine the micro-foundations and assumptions of economic agents with an Islamic perspective. The basic understanding of normative goals in life, incentives and how they relate to economic behaviour and activities are discussed. We also propose some important micro foundations from an Islamic perspective to be considered in teaching microeconomics. The points addressed in this chapter can be regarded as an integration effort in teaching the subject. In the integration process, the learning objective is for students not just to understand the conventional microeconomic but they also need to be exposed to the Islamic perspective on certain topics of the subject. For that, selected points on conventional micro foundation related to goals, incentives and behaviour are compared with Islamic micro foundations. Instructors need to ensure that students get the correct understanding of conventional microeconomics before integrating the Islamic perspective to the students.